Transformasi Teknologi Digitalisasi Arsip sebagai Upaya Optimalisasi Administrasi Pemerintahan Desa yang Efisien - Munawir, Munawir; Irwansyah, Irwansyah; Hasibuan, Ade Zulkarnain (JPM: Jurnal Pengabdian Masyarakat, 2025)
Archive digitalization is an essential step in improving the efficiency of document management at the village government level. Currently, archiving processes are still carried out manually using paper-based media, which creates several problems such as the risk of damage and data loss, difficulties in document retrieval, limited storage space, and slow administrative services to the community. The purpose of this community service activity is to enhance administrative efficiency and strengthen the competence of village officials through the implementation of a digital archive system. The solution offered is the development and implementation of a web-based digital archive application accompanied by training and technical assistance for village officials. The application was developed using CodeIgniter, Bootstrap, and MySQL technologies to ensure user-friendliness, fast access, and structured data management. The implementation methods include needs analysis, system design, application implementation, training, and intensive mentoring. The results show that the digital archive application improved administrative efficiency, accelerated document retrieval, and reduced the risk of archive loss. Moreover, village officials gained increased competence in managing digital archives. Therefore, this system has the potential to serve as a model for other villages in optimizing administrative services through archive digitalization.